2020
DOI: 10.1177/1550059420965385
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Resting EEG in Hallucinating and Nonhallucinating Schizophrenia Patients

Abstract: Auditory hallucinations (AHs) are a common symptom of schizophrenia and contribute significantly to disease burden. Research on schizophrenia and AHs is limited and fails to adequately address the effect of AHs on resting EEG in patients with schizophrenia. This study assessed changes in frequency bands (delta, theta, alpha, beta) of resting EEG taken from hallucinating patients (n = 12), nonhallucinating patients (n = 11), and healthy controls (n = 12). Delta and theta activity were unaffected by AHs but diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 60 publications
(97 reference statements)
0
6
0
Order By: Relevance
“…Although, Van Lutterveld, Hillebrand, et al (2012) found experiencing AH was associated with reduced theta-band power (in the right hippocampus), Ishii et al (2000) found that experiences of AH were associated with increased theta-band activity. Other studies have failed to find alterations of theta power to be associated with AH, finding such changes to relate to schizophrenia per se instead (Arora et al, 2021). There is hence a need for a clearer picture of the role (if any) of theta-band changes in relation to AH.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Although, Van Lutterveld, Hillebrand, et al (2012) found experiencing AH was associated with reduced theta-band power (in the right hippocampus), Ishii et al (2000) found that experiences of AH were associated with increased theta-band activity. Other studies have failed to find alterations of theta power to be associated with AH, finding such changes to relate to schizophrenia per se instead (Arora et al, 2021). There is hence a need for a clearer picture of the role (if any) of theta-band changes in relation to AH.…”
Section: Discussionmentioning
confidence: 98%
“…In terms of alpha-band power, the work of Arora et al (2021) has provided evidence of lower alpha activity in frontal areas bilaterally being associated with both trait and state AH. Similarly, Van Lutterveld, Hillebrand, et al (2012) found state experiences of AH were associated with a decrease in alpha-band power (specifically in the right inferior frontal gyrus).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the parameters checked to measure performance are: {R}{e}{c}{a}{l}{l} \left({\%}\right)=\frac{{T}{P}}{{T}{P}+{F}{N}} {x} 100 (6) {S}{p}{e}{c}{i}{f}{i}{c}{i}{t}{y} \left({\%}\right)=\frac{{T}{N}}{{T}{N}+{F}{P}} {x} 100 (7) {P}{r}{e}{c}{i}{s}{i}{o}{n} \left({\%}\right)=\frac{{T}{P}}{{F}{P}+{F}{P}} {x} 100 (8) {B}{a}{l}{a}{n}{c}{e}{d} {a}{c}{c}{u}{r}{a}{c}{y} \left({\%}\right)=\frac{{R}{e}{c}{a}{l}{l}+{S}{p}{e}{c}{i}{f}{i}{c}{i}{t} {y}}{2} {x} 100 (9) In these equations, TP indicates the number of positive cases, TN is the true negatives, FN the false negatives and FP indicates the false positive cases. In addition, the {{F}}_{1} score and Matthew's correlation coe cient (MCC) were employed during the study.…”
Section: Validationmentioning
confidence: 99%
“…Currently, there is no objective examinations that can con rm the disease. Nevertheless, the monitoring of neurophysiological activity through encephalograms (EEGs) provides decisive information that can lead to a possible diagnosis [8][9][10][11]. EEGs offers an effective means of evaluating brain function, remaining an essential tool in neurology, particularly in serious neurological conditions.…”
Section: Introductionmentioning
confidence: 99%